Potential role of glucagon like peptide 1 in taste receptors - Doval-Caballero, Jose Luis Eduardo; Ferreira-Hermosillo, Aldo; Eugenio-Ponce, Genesis Dinora; García-Sáenz, Manuel Ramon; Ibarra-Salce, Raúl; Tenorio-Rojo, Andrea Patricia; Luna-Avila, Eduardo Salif; Gete-Palacios, Paulo César; Pérez-Hernández, Fernando; Rojas-Milán, Eduardo; López-Cruz, Luis Angel; Méndez-Hernández, César Alejandro (Frontiers in Endocrinology, 2026)
The perception of taste is a complex physiological process that extends far beyond the simple detection of flavor molecules, serving as a critical interface between nutrient sensing, metabolic regulation, and feeding behavior. Emerging evidence reveals that this process is profoundly modulated by endocrine and neuromodulatory systems, creating a sophisticated gut-brain-taste axis that integrates peripheral gustatory signals with central homeostatic and hedonic mechanisms. Hormones such as glucagon-like peptide-1, leptin, ghrelin, and CCK not only regulate appetite and energy balance but also directly influence taste receptor expression and function in the tongue and gastrointestinal tract. Concurrently, neuromodulators like dopamine, serotonin, and norepinephrine fine-tune taste sensitivity at both peripheral (taste buds) and central (reward circuitry) levels, linking chemosensation to motivational states. These interactions are further complicated by metabolic conditions such as obesity and diabetes, where hormonal resistance (e.g., leptin, insulin) and neurotransmitter dysregulation contribute to altered taste preferences and compulsive eating behaviors.